ANALYSIS OF TRANSLATION TECHNIQUES IN THE ENGLISH SUBTITLE OF THE MOVIE "KETIKA CINTA BERTASBIH 1" - Mujad Didien Afandi; Nailul Authar (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
A mistake in translating a single word may cause thousands of deaths. An unimaginable fact that mistranslation cost 80.000 lives in Japan in August 1945 proves that translating a text should be taken into consideration and done carefully. Translating a source language (SL) into a target language (TL) is problematic and not as simple as only transposing SL into TL because this activity closely relates to different cultures. Therefore, this study is aimed at analyzing the translation techniques in the English subtitle of the movie “Ketika Cinta Bertasbih 1”. This qualitative study focuses on Molina and Albir’s translation techniques used in the English movie subtitle. The primary data were collected from the dialogs and the English subtitle and selected based on the translation problems. Furthermore, the data were analyzed and interpreted descriptively to identify and explain why and how the translation techniques are used in the English subtitle. This study found that five translation techniques were used to translate the dialogs in bahasa Indonesia (SL) into English subtitle (TL). In the subtitle, this study found the use of adaptation (10 times), transposition (9 times), borrowing (7 times), generalization (3 times) and compensation (once). Those techniques were applied to solve problems in translation, such as cultural differences, in equivalence, untranslatability, and grammatical differences. This study concludes that the techniques proposed by Molina and Albir in 2002 have been a great contribution in the field of translation. The cultural problems which lead to in equivalence and untranslatability, as well as grammatical differences are no longer problematic to translators.